Importance of Autoimmune Responses in Progression of Retinal Degeneration Initiated by Gene Mutations - Adamus, Grazyna (Frontiers in Medicine, 2021)
Inherited retinal diseases (IRDs) are clinically and genetically heterogeneous rare disorders associated with retinal dysfunction and death of retinal photoreceptor cells, leading to blindness. Among the most frequent and severe forms of those retinopathies is retinitis pigmentosa (RP) that affects 1:4,000 individuals worldwide. The genes that have been implicated in RP are associated with the proteins present in photoreceptor cells or retinal pigment epithelium (RPE). Asymmetric presentation or sudden progression in retinal disease suggests that a gene mutation alone might not be responsible for retinal degeneration. Immune responses could directly target the retina or be site effect of immunity as a bystander deterioration. Autoantibodies against retinal autoantigens have been found in RP, which led to a hypothesis that autoimmunity could be responsible for the progression of photoreceptor cell death initiated by a genetic mutation. The other contributory factor to retinal degeneration is inflammation that activates the innate immune mechanisms, such as complement. If autoimmune responses contribute to the progression of retinopathy, this could have an implication on treatment, such as gene replacement therapy. In this review, we provide a perspective on the current role of autoimmunity/immunity in RP pathophysiology.